Bacterial-stimulated cytokine production of peripheral mononuclear cells from patients of various periodontitis categories - Kjeldsen, M; Holmstrup, P; Lindemann, R A; Bendtzen, K (Journal of periodontology (1970), 1995)
Periodontitis is a general term for disease categories, including juvenile periodontitis (JP), rapidly progressive periodontitis (RPP), and adult periodontitis (AP), which may or may not share a common etiology and pathogenesis. These disease categories are characterized by differences in progression of tissue destruction and differences in age group susceptibility, but not, to our knowledge, by differences in cytokine responses of inflammatory cells. The present study examined blood cell counts and interindividual variation in the ability of PBMC of patients in three different categories of periodontitis to produce cytokines after stimulation with different oral bacterial species in vitro. The AP group had a significantly lower production of IL-1ra when stimulated with Porphyromonas gingivalis (P.g.) and Actinobacillus actinomycetemcomitans (A.a.) (P < 0.05). Streptococcus sanguis (S.s.), which is associated with normal periodontal conditions, induced extremely high levels of IL-1 alpha and TNF alpha production in all groups. The RPP group had a significantly higher number of monocytes (MC) than the AP group (P < 0.05). Additionally, JP patients had a significantly higher concentration of polymorphonuclear granulocytes compared to juvenile controls (P < 0.05). In conclusion, IL-1 alpha, TNF alpha, or IL-6 production by peripheral blood MC after in vitro stimulation with oral bacterial type stains may not distinguish different categories of periodontitis. The results support the hypothesis that the cytokine IL-1ra is produced in different concentrations in the two groups: RPP and AP. Furthermore, elevated MC concentration in the RPP group compared to the AP group may be an important pathogenic feature in RPP.